BIG data - BIG gains? Empirical evidence on the link between big data analytics and innovation - Thomas Niebel; Fabienne Rasel; Steffen Viete (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
This paper analyzes the relationship between firms' use of big data analytics and their innovative performance in terms of product innovations. Since big data technologies provide new data information practices, they create novel decision-making possibilities, which are widely believed to support firms' innovation process. Applying German firm-level data within a knowledge production function framework we find suggestive evidence that big data analytics is a relevant determinant for the likelihood of a firm becoming a product innovator as well as for the market success of product innovations. These results hold for the manufacturing as well as for the service sector but are contingent on firms' investment in IT-specific skills. Subsequent analyses suggest that firms in the manufacturing and service sector rely on different data sources and data-related firm practices in order to reap the benefits of big data. Overall, the results support the view that big data analytics have the potential to enable innovation.
urn:nbn:de:bsz:180-madoc-437068
Keywords: D22; L20; O33; 330; big data; data-driven decision-making; product innovation; firm-level data